Bloom's Cognitive Abilities during Pandemic Corona: "Video versus Simulated Video" the best Learning Strategy that enhances the higher ability - Allouch, Amena; Nasserddin, Sultan; Ghaddar, Faddel (Technium Social Sciences Journal, 2021)
A successful learning process is ensured by applying various teaching strategies. Corona Pandemic has forced teachers to teach through new distant educational sources, hence specific learning strategies must be applied by them. Thus the primary objective of this study is to investigate: 1) Distance learning strategies that are available to be used by science teachers 2) The best learning strategy to enhance the higher cognitive abilities or skills. 46 respondents from different levels were randomly chosen from Safir High School in South Lebanon. A questionnaire was used to investigate the teaching strategies used by the chemistry teachers. Two different learning strategies were applied on two groups (23 students each) one using a video only and the other using a video and a simulated video, each group performed a bloom's assessment after the learning session which included six questions listed in order from the lowest cognitive skill to the higher cognitive skill. Wilcoxon signed-rank test was applied to compare the two paired groups and to specify if the two sets are different from one another in a statistically significant manner. The results emphasized that the type of teaching strategy applied does affect the level of the cognitive skills that can be reached by students, using a simulated video proved to be the more effective strategy, were the vast majority of students reached the higher cognitive level "create" in contrary to just using a video, teachers should be aware of the effects of the learning strategies they choose on learning enhancement.